2014
DOI: 10.1002/cem.2690
|View full text |Cite
|
Sign up to set email alerts
|

A study on the differential strategy of some iterative trilinear decomposition algorithms: PARAFAC‐ALS, ATLD, SWATLD, and APTLD

Abstract: This study presents an in‐depth discussion of the differential properties of various iterative trilinear decomposition algorithms, including Parallel Factor Analysis‐Alternating Least Squares (PARAFAC‐ALS), Alternating Trilinear Decomposition (ATLD), Self‐Weighted Alternating Trilinear Decomposition (SWATLD), and Alternating Penalty Trilinear Decomposition (APTLD). The shape of each algorithm's objective function (“convex” or “strictly convex”) is related to the algorithm's sensitivity to the estimated compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…ATLD holds the fastest convergence, which is attributed to the operation based on sliced matrices with less size and two other major strategies. One is the truncated least-squares method, which uses the tolerance to truncate the small singular values in the singular value decomposition; the other is the operation of selecting diagonal elements, which also makes ATLD retaining trilinearity property indeed and be insensitive to the overestimated number of components [54,55]. As long as the selected number of components is equal to or greater than the underlying real number of components, the ATLD method can provide correct decomposed profiles, and the excess components always appear in the shapes of noises which are easily recognized.…”
Section: Alternating Trilinear Decomposition (Atld) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATLD holds the fastest convergence, which is attributed to the operation based on sliced matrices with less size and two other major strategies. One is the truncated least-squares method, which uses the tolerance to truncate the small singular values in the singular value decomposition; the other is the operation of selecting diagonal elements, which also makes ATLD retaining trilinearity property indeed and be insensitive to the overestimated number of components [54,55]. As long as the selected number of components is equal to or greater than the underlying real number of components, the ATLD method can provide correct decomposed profiles, and the excess components always appear in the shapes of noises which are easily recognized.…”
Section: Alternating Trilinear Decomposition (Atld) Methodsmentioning
confidence: 99%
“…Therefore, ATLD method became the best candidate to analyze the three-way large-scale LC-MS experimental data. More detailed information for ATLD method can be found in the previously published references [44,[54][55][56][57].…”
Section: Alternating Trilinear Decomposition (Atld) Methodsmentioning
confidence: 99%
“…However, it is worth noting that there is not a single versatile method that is appropriate for all situations because every method has its own advantages and disadvantages [32], and the fields of application of these methods are not the same. Some reports have compared the properties of these methods from the perspectives of theory and application [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…It can quantitatively measure the specific components in the existence of interferents [16][17][18]. But only estimating the component number correctly can we get the accurate result [19,20]. The self-weighted alternating trilinear decomposition (SWATLD) algorithm, which has been developed in recent years, is insensitive to component numbers, requires fewer iterations and has high stability [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…But only estimating the component number correctly can we get the accurate result [19,20]. The self-weighted alternating trilinear decomposition (SWATLD) algorithm, which has been developed in recent years, is insensitive to component numbers, requires fewer iterations and has high stability [20][21][22]. Hu and Yin applied PARAFAC-alternative least squares (PARAFAC-ALSs) and SWATLD to measure Vancomycin and Cephalexin in human plasma, the experimental result showed that SWATLD algorithm had good effect on the determination of complex analysis of drugs in plasma [23].…”
Section: Introductionmentioning
confidence: 99%